Promoting a culture of sharing the error: A qualitative study in resident physicians' process of coping and learning through self-disclosure after medical error - Asakawa, Mari; Imafuku, Rintaro; Kawakami, Chihiro; Hayakawa, Kaho; Suzuki, Yasuyuki; Saiki, Takuya (Frontiers in Medicine, 2022)
Purpose: Most physicians, including residents, experience significant emotional distress as second victims after making medica11l errors. As high reliability organizations (HROs), hospitals must not only support physicians’ emotional recovery but also promote their learning from errors. Self-disclosure is a process of communication in which individuals reveal information about themselves to others. While many previous studies have focused on investigating the effectiveness of self-disclosure, little is known about the process itself. Therefore, this study aims to explore residents’ processes of coping with their emotional distress and learning through self-disclosure after making errors. Methods: Semi-structured interviews were conducted with 22 residents in their second year from two Japanese hospitals where informal error conferences guided by senior residents are implemented regularly. In the interview, four core questions were posed regarding the nature of the error/incident, their emotions and behavior after the error, ways of self-disclosure, and the results of error-sharing in the conference. Interview data were thematically analyzed, drawing upon disclosure decision model as the theoretical framework. Results: Five phases emerged from the analysis: 1) emotional distress and reactions before self-disclosure; 2) self-disclosure to individuals to achieve social rewards; 3) emotional sublimation after self-disclosure to individuals; 4) sharing errors in groups for learning opportunities; and 5) transforming the perspectives on overcoming and learning from errors. Conclusion: This is the study to demonstrate that various types of self-disclosure were embedded in the processes of residents’ recovery and learning from medical errors. The study suggests that a better understanding of the processes of residents’ coping with their distress and learning from their errors through self-disclosure is fundamental to the creation of a “culture of sharing errors” in hospitals as HROs.